Optical characterisation of silicon nanocrystals embedded in SiO(2)/Si(3)N(4 )hybrid matrix for third generation photovoltaics - Di, Dawei (Springer, 2011)
Silicon nanocrystals with an average size of approximately 4 nm dispersed in SiO(2)/Si(3)N(4 )hybrid matrix have been synthesised by magnetron sputtering followed by a high-temperature anneal. To gain understanding of the photon absorption and emission mechanisms of this material, several samples are characterised optically via spectroscopy and photoluminescence measurements. The values of optical band gap are extracted from interference-minimised absorption and luminescence spectra. Measurement results suggest that these nanocrystals exhibit transitions of both direct and indirect types. Possible mechanisms of absorption and emission as well as an estimation of exciton binding energy are also discussed.